PROBLEMS AND PROSPECTS OF IMPLEMENTATION OF THE POLICY OF IMPORT SUBSTITUTION IN INDUSTRY OF THE NORTH CAUCASIAN FEDERAL DISTRICT - Natalia Borovikova; Anna Ter-Grigoryants (Вестник Северо-Кавказского федерального университета, 2022)
On the basis of the study of the evolution of scientific thought in the field of industry placement in space, the necessity of implementation of the economic policy of import substitution in certain territorial entities is proved. Identification of problems of development and implementation of import substitution policy in the North Caucasus allowed to formulate the main directions of ensuring the long-term effectiveness of industrial policy in the regions of the North Caucasus Federal district, taking into account global trends and modern achievements of science and technology.